THE STATE OF ART EDUCATIONAL INSTITUTIONS IN UKRAINE DURING THE PERIOD OF UKRAINIZATION (Physical Culture and Sport: Scientific Perspective, 2022)
The article highlights the historical contexts within which Ukrainian society existed in the 20s of the 20th century. The historical concept of "Ukrainization", its differences from the meaning of the term "Derussification" is revealed, and the mastered characteristic feature of this period of time is revealed. The researchers and scientific currents that studied art education during the times of "Ukrainization" were identified, the central tasks of the scientific work were highlighted. The general features and situation of art education were analyzed, a number of educational institutions were singled out, which had a narrow-profile nature of teaching fine arts. The main features of domestic art educational institutions during the period of Ukrainization are determined. The characteristic features of these art educational institutions in Ukraine at the time of Ukrainization in the 1920s are described separately. The individual features of the educational art institution were formulated, which were formed due to the reasons of the territorial location, the relationship between society and the government, the relevance of the type of artistic disciplines (which they offered) and, accordingly, the level and status of the institution. The structural elements of the educational process in the existing professional institutions of the outlined period of time are presented in detail. Each of the parts of the analysis of art education institutions is recorded by famous graduates-artists, teachers, professors, art critics and masters of the 20s of the 20th century. The state of reform and structural transformations of art education institutions is summarized. Further creative and pedagogical activities of graduates of these art educational institutions are separately determined. A brief description of the activities of artists, teachers and professors who received primary or higher education in the described art schools was made. The results of further creative work (the key themes of creative activity, when and at what levels were the exhibitions of R. Lislvskyi, Z. Okhrimovych, O. Shovkunenko and others), pedagogical work (what position did V. Sedlyar, S. Byesedin work in) and scientific work were formulated (on the example of the combination of creative, scientific and pedagogical activities of the artist V. Sedlyar) of the Ukrainian artistic community.
Keywords: Ukrainization; De-Russification; art education; training; art institution